Architectural and structural drawing for davit arm including TDS & weight (RFA-001_Rev.C) - Fabcons Construction & Fabrication (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.